Incidence and risk factors of low birth weight babies born in Dhulikhel Hospital - Singh, SD; Shrestha, S; Marahatta, SB (Journal of Institute of Medicine Nepal, 2011)
Introduction: WHO defines low birth weight (LBW) as a birth weight less than 2500 grams. Almost a third of the newborn in South East Asia Region is a low birth weight baby. Many risk factors contributing to LBW have been recognized, which in order of importance are low maternal weight, low maternal hemoglobin, low maternal height, primi-parity, adolescent mother and poor or inadequate maternal nutrition during pregnancy. Low birth weight babies have a higher risk of morbidity and mortality than an infant of normal birth weight. The present study was carried out to explore the associated risk factors of low birth weight which will be beneficial to undertake effective measures to reduce the burden of the low birth weight. Methods: This was a hospital based case control study conducted in Dhulikhel hospital, Kavre, Nepal from Jan 1st 2008 to 30th May 2010. A total of 401 cases and an equal number of age matched controls were taken to assess the different risk factors of the mother for LBW babies. Ethical approval for the study was taken from KUSMS-Institutional research committee. Data analysis was done using SPSS version 10.0. Results: Data of 401 LBW and equal number of normal birth weight babies were analyzed. The incidence of LBW in this study was 11.07%. LBW was more common in female (n=236) than in male (n=165) babies. However this difference was statistically insignificant. Among the case and the control group, maternal hemoglobin (p<0.001), maternal height (p<0.001), maternal weight gain (p<0.0001), number of ANC visits (p<0.0001) were statistically significant. However with regards to ethnicity, nutrition during pregnancy, parity and age of the mother the association were insignificant. Ethnical group, nutrition during pregnancy, age of mother and parity was found to be statically insignificant for LBW Conclusions: LBW is a common problem of the developing world, which is an important factor for perinatal mortality and morbidity. Maternal height, hemoglobin, total weight gain and ANC visit were found to be the significant risk factors contributing to LBW DOI: http://dx.doi.org/10.3126/joim.v32i3.4959 Journal of Institute of Medicine, December, 2010; 32:3 39-42